Linear porokeratosis. A case report. - Sahin, M.T.; Öztürkcan, S.; Türel, A.; Kandiloglu, A.R. (European Journal of Pediatric Dermatology, 2002)
Linear porokeratosis (LP) is a rare variant of porokeratosis of Mibelli. It is a disorder of keratinization, which consists of atrophic lesions with a raised horny margin. The cause is quite unknown. No definite inheritance pattern has been established. Among the five clinical forms of porokeratosis of Mibelli (PM), LP represents the segmental form, in which porokeratotic lesions are arranged in a linear fashion, usually corresponding to a dermatome or Blaschko's lines. The condition is strictly unilateral and onset is usually in infancy and childhood. There is slight risk of malignant transformation. We report a 16-year-old girl with a 14-year history of typical lesions in a linear arrangement on the dorsal aspect of her right leg, which were diagnosed as linear porokeratosis based on the clinical and histopathological features.